Penganggaran Sekolah Berbasis Kinerja (Studi Kasus Pada SMP Negeri 30 Medokan Semampir, Kecamatan Sukolilo, Surabaya) - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; SUPRIYANTO SUPRIYANTO (FISIP UWP, 2010)
Budgeting is very important activity to make organization (public or private) to obtain it goals better, faster, and fulfilling the hope from all people inside. This research purpose to looking how far the formulation process of Performance Based Budgeting in SMPN 30 Surabaya and any impact factors inside them. Budgeting measurement by using performance indicators is, input, output, efficiency, and outcome. The impact factors has been looked from external environments, vision, and mission.